Effects of hypercapnia on T cells in lung ischemia/reperfusion injury after lung transplantation. (December 2014) - Gao, Wei; Liu, Dongdong; Li, Di; Che, Xiangyu; Cui, Guangxiao
T cells play a key role in lung ischemia/reperfusion injury (IRI). Hypercapnia has been indicated to decrease IRI and inhibit immunity. This study aimed to evaluate the effects of hypercapnia on T cells during lung IRI and to identify the underlying mechanism of these effects. In the in vivo study, rat recipients of lung transplants were randomized into a control group M and a hypercapnia group H. Peripheral blood T cells and cytokines were analyzed during reperfusion. In the in vitro study, we analyzed the T cells and cytokine levels in culture media from phytohemagglutinin-stimulated T cells from normal rats, stimulated under the normal (group C), hypercapnic (group H), or buffer hypercapnic (group BH) condition. In the in vivo study, the CD3 + /CD4 + T-cell ratio and interleukin (IL)-2, IL-8, interferon (IFN)-γ, intracellular adhesion molecule (ICAM)-1, and P-selectin levels were decreased, but the IL-4 and IL-10 levels were increased, after reperfusion in group H compared to group M. In the in vitro study, groups H and BH exhibited a decreased CD2 + /CD28 + ratio and IL-2 and IFN-γ levels, but elevated IL-4 and IL-10 levels, compared to group C. The CD2 + /CD28 + ratio was not different between groups BH and H; however, group H evidenced a lower IL-2 level and higher IL-4 and IL-10 levels compared to group BH. Hypercapnia decreased the CD3 + /CD4 + T-cell ratio and pro-inflammatory cytokine levels, but promoted anti-inflammatory factors in lung IRI. Hypercapnia inhibits CD2 and CD28 in T cells by CO2 and modulates T-cell cytokines via acidosis.